Pengembangan Kapasitas Pokdarwis Melalui Pelatihan Standar Pengelolaan Homestay dan Pemasaran Produk Wisata Berbasis Masyarakat di Kelurahan Guntung Bontang - Said Keliwar; Anton Nurcahyo; Rini Koen Iswandari (Universitas Muhammadiyah Semarang, 2023)
Guntung is one of the villages in North Bontang Sub-district, Bontang City, which has diverse tourism resources. However, there are several problems faced by the Guntung communities, especially the Benua Etam Tourism Awareness Group (Pokdarwis) and the tourism business communities. These problems include the management and development of standardized homestays and marketing of tourism products based on the Guntung community (Community Based Tourism). This service aims to increase the capacity of Pokdarwis Human Resources and the community of Guntung Village in managing and developing a standardized homestay business and the ability to market tourism village products in Guntung Village.The stages and methods used in this community service training consist of 3 (three) stages; namely the preparation stage, the implementation stage, and the evaluation stage with lecture, discussion, question and answer, field trip and role play methods. Based on the results obtained from community service activities, it shows that Pokdarwis and tourism business actors are able to apply homestay management standards to their businesses and have the ability to do marketing, especially promotion by utilizing Intstagram social media.